Using Systematic Observation and Polar Coordinates Analysis to Assess Gender-Based Differences in Park Use in Barcelona - Pérez-Tejera, Félix; Valera, Sergi; Anguera, M. Teresa (Frontiers in Psychology, 2018)
This paper aims to assess gender differences in the usage of public open spaces (POS), as an everyday context. Forty POS in the city of Barcelona were studied over 3 months using systematic observation. To objectively measure park use, an observational instrument (EXOdES) was purposely designed combining a field format and several category systems. The instrument facilitated the record of more than 35.000 configurations or co-occurrences of codes from different dimensions (e.g., location, types of users, activities and environmental features), providing contextually rich data based on individuals, groups and the setting in which the activity occurs. The control of quality of data has been done through Cohen’s coefficient and it has been highly satisfactory. A similar proportion of males and females were found using POS (55% vs 45%). To identify regular patterns in the way that men and women use public space, information on more than 18,000 groups of people was analysed as a global data set. A multievent sequential analysis was performed considering gender composition as the given behaviors (i.e., groups of males, females and gendered mixed) and a reduced number of criteria of the observational instrument as the target criteria (i.e., time of day, age, race/ethnicity, location, activity and vehicles). Thus, polar coordinates analysis was also performed, because it is a suitable reduction data technique in studies with a broad observational instrument and a large database. Results show important gendered and cultural differences in POS use. Women tend to reproduce traditional gender role, being often more engaged in care functions with children and elders rather than in any other activity or with people of their same age group. Of particular concern is the gap on park use observed in women of ethnic minority groups.